ChemInform Abstract: Metal/Semiconductor Hybrid Nanostructures for Plasmon‐Enhanced Applications. Issue 40 (30th September 2014) - Jiang, Ruibin; Li, Benxia; Fang, Caihong; Wang, Jianfang
Abstract Review: 295 refs.